#### Answer

$f(x)=\sqrt[3] x$ and $g(x)=x^2-9$
(Other solutions are possible.)

#### Work Step by Step

One possible solution is:
$f(x)=\sqrt[3] x$ and $g(x)=x^2-9$, such that $h(x)=(f\circ g)(x)$

Published by
Pearson

ISBN 10:
0-13446-914-3

ISBN 13:
978-0-13446-914-0

$f(x)=\sqrt[3] x$ and $g(x)=x^2-9$
(Other solutions are possible.)

One possible solution is:
$f(x)=\sqrt[3] x$ and $g(x)=x^2-9$, such that $h(x)=(f\circ g)(x)$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.